Clinical efficacy of Bucillamine for childhood rheumatic disease - Nagata, Masato; Satou, Tatsuya; Tatsuzawa, Osamu; Koike, Yuichi (Ensho, 1994)
Bucillamine (1.6-3.0 mg/kg/day) was administered to 9 children with rheumatic diseases resistant to aspirin. The usefulness was evaluated based on improvement in the functional impairments and other symptoms at 12 weeks and 1 year after administration. The results disclosed evidence that clinical improvement with decreased numbers of painfull joints in 7 cases (5 cases with polyarticular type JRA, 1 case with juvenile chronic arthritis and 1 case with spondyloarthropathy) . Stomatitis was found in 2 cases and proteinurea in 1 case as adverse effects. Bucillamine was useful for children with rheumatic diseases to whom nonsteroidal antiinflammatory drug was ineffective.